An Exploration of Students' Perceptions Toward Crossword Puzzle Game-Based Learning in Enhancing Motivation to Learn English Vocabulary - Anita; Meristika Moetia (Journal Informatic, Education and Management (JIEM), 2025)
Vocabulary mastery is a crucial component in English as a Foreign Language learning, as it directly influences students’ ability to listen, speak, read, and write effectively. However, many junior high school students demonstrate low motivation when learning vocabulary through conventional, lecture-based methods. This study aimed to explore students’ perceptions of using crossword puzzles as a medium for learning English vocabulary and its impact on their learning motivation. A descriptive qualitative design was employed, involving seventh-grade students from MTsN 3 Aceh Barat Daya. One class of 30 students was purposively selected as the sample. Data were collected through semi-structured interviews, classroom observations, and documentation, then analyzed using Miles and Huberman’s (1994) interactive model. The findings reveal that crossword puzzles significantly increased students’ motivation, engagement, and vocabulary retention. Students reported enjoying the challenge and collaborating actively with peers, while observations showed high levels of participation and persistence in completing the tasks. The study concludes that crossword puzzles provide a simple, flexible, and effective strategy for fostering emotional, cognitive, and social engagement in vocabulary learning, and they can be adapted for other foreign language contexts to address low learning motivation